GEOLOGY OF SUNGAI SIPUT LIMESTONE QUARRY WITH EMPHASIS ON SOME PETROPHYSICAL CHARACTERISTICS - Bin Hamidun Majid , Nazmy Amir (Universiti Teknologi PETRONAS, 2014)
This project is about the sedimentation and petrophysical characteristics of limestone found in Sungai Siput. The area is mostly made up of limestone hills that were remnants of massive carbonate beds covered with alluvial sediments. This research will provide geological study of the area as well as providing a geological map of the study area. The study is divided into two parts in which the first part is the geological mapping of the area followed by the relation of carbonate facies to the petrophysical properties of the area. The study also includes a number of test such as porosity and permeability, to measure reservoir quality of limestone found in the area, and thin section analysis which allows us to determine and examine the mineral composition found in the rock.